Analisis Yuridis Pengawasan Partisipatif Masyarakat sebagai Upaya Pencegahan Pelanggaran Pemilihan Umum - Muhammad Erfandi; Herdy Pratama Susantyo (AHKAM, 2025)
Upholding integrity in the administration of general elections (Pemilu) is a crucial aspect of safeguarding the quality of democracy in Indonesia. One strategic approach to preventing electoral violations is participatory supervision, which involves the active engagement of the public. This study aims to analyze, from a juridical perspective, the forms, mechanisms, and effectiveness of participatory supervision within the Indonesian legal framework as an instrument for preventing election violations. A normative juridical method was employed by examining key regulations, such as Law No. 7 of 2017 on General Elections, alongside various technical provisions issued by the Election Supervisory Agency (Bawaslu). The findings indicate that participatory supervision plays a vital role in ensuring elections are conducted fairly, honestly, transparently, and cleanly, by encouraging voters to engage intelligently through data collection, violation reporting, and information dissemination. Nevertheless, its effectiveness in practice faces several challenges, including limited public understanding, insufficient outreach by election organizers, and institutional capacity constraints. The study concludes that participatory supervision is a strategic tool for preventing electoral violations, yet it requires regulatory strengthening, continuous political education, and synergy between Bawaslu, stakeholders, and civil society to be effectively and sustainably implemented.